Respuesta :
Answer:
41
Step-by-step explanation:
substitute x=-2 and y=6, we know
8×6 +4×(-2) -(2×(-2) +3) = 48-8-(-1) =41
Answer:
41
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
- Left to Right
Step-by-step explanation:
Step 1: Define
Identify
8y + 4x - (2x + 3)
x = -2
y = 6
Step 2: Evaluate
- Substitute in variables: 8(6) + 4(-2) - (2 · -2 + 3)
- (Parenthesis) Multiply: 48 - 8 - (-4 + 3)
- (Parenthesis) Add: 48 - 8 - (-1)
- Subtract: 41